An eocene articulated polyplacophora (Mollusca) from the La Meseta Formation, Antarctica and the stratigraphy of the fossil-bearing strata - Lopez Cabrera O., Maria Isabel; Olivero, Eduardo Bernardo (Journal of Paleontology)
An exceptionally well-preserved specimen of Leptochiton sp. attached to a brachiopod valve is described from the early Eocene beds of the La Meseta Formation, Seymour Island. It records the first fossil Polyplacophora from Antarctica. The small specimen has eight imbricating valves, rounded lateral margins, ribs of fine granules, and growth marks in all valves. It strongly resembles extant Antarctic and South American species of Leptochiton Gray. The record of articulate valves in fossil Polyplacophora is rare and requires exceptional preservational conditions. Leptochiton sp. is associated with well preserved bryozoans, brachiopods, asterozoan echinoids, and serpulids, among other organisms that inhabited hard substrates in normal marine conditions, and probably lived attached to the side walls of an incised valley eroded in Cretaceous sediments. The well-preserved fossils were probably removed from their attachment site during storm events and, after a short transportation, rapidly buried within the early Eocene valley-fill deposits. The fossil-bearing beds are included in the Telm 2 or Acantilados Allomember of the La Meseta Formation. Fil: Lopez Cabrera O., Maria Isabel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina